A comparison between photovoltaic and solar thermal power generation technologies - Farias dos Santos, Thiago; Dal Forno, Ana Julia (Latin American Journal of Energy Research, 2024)
This article aimed to compare solar photovoltaic (PV) and concentrated solar thermal (CSP) technologies for generating electricity as a preliminary criterion for choosing this type of renewable energy source. The particularities, technical and economic characteristics, operating methods and other features of each were presented. In order to determine in which situations PV and CSP systems are more viable for implementation, analyses of electricity generation in different scenarios, both current and future, were carried out, using the levelized cost of electricity (LCOE) metric, the capacity factor, the area required for installation, among others. The results obtained demonstrated that the advantages of PV generation are: lower LCOE cost, generation of energy with direct and diffuse radiation, modularity and simplicity of installation and generation of energy after its installation. On the other hand, the main differentials of CSP technology are a higher capacity factor and consequent energy storage, and the possibility of hybrid operation. Thus, was observed that the choice of the type of solar power generation technology will depend on several factors in addition to those obtained using the levelized cost of electricity metric.